ANALISIS PROGRAM ZERO WASTE TO LANDFILL MENGGUNAKAN SISTEM MANAJEMEN LINGKUNGAN ISO 14001:2015 DI TAMAN MARGASATWA RAGUNAN TAHUN 2023 - Mohammad Rayhan Hernadi (2023)
Indonesia waste in 2022 increased by 2.2 million tons. One of the contributors to waste in Jakarta is Ragunan Zoo, which has experienced a 550% increase waste generation. Realizing Zero Waste to Landfill program, Ragunan Zoo needs to apply ISO 14001:2015 Environmental Management System. This research aims to obtain in-depth information about Zero Waste to Landfill program at Ragunan Zoo. The study used a qualitative method with Rapid Assessment Procedure to adjust the implementation of waste management based on ISO 14001:2015 EMS. Methods of data collection through in-depth interviews with validation using triangulation methods, sources, and theories. There are seven informants divided into two, managers and visitors. Based on the results of data analysis, Ragunan Zoo has implemented good waste management program by not transporting waste to Landfill. Planning and implementation are almost aligned with the requirements of ISO 14001:2015, but evaluation and continuous improvement needs to be revisited. To be approved, TMR needs to meet the requirements of ISO 14001: 2015 clause which is lacking especially on environmental policies, compliance, waste recovery, and non-conformities and corrective actions if want to implement the EMS.